Synergies and Entanglement in Secondary Cell Wall Development and Abiotic Stress Response in Trees - Coleman, Heather D.; Brunner, Amy M.; Tsai, Chung-Jui (Frontiers in Plant Science, 2021)
A major challenge for sustainable food, fuel, and fiber production is simultaneous genetic improvement of yield, biomass quality, and resilience to episodic environmental stress and climate change. For Populus and other forest trees, quality traits involve alterations in the secondary cell wall (SCW) of wood for traditional uses, as well as for a growing diversity of biofuels and bioproducts. Alterations in wood properties that are desirable for specific end uses can have negative effects on growth and stress tolerance. Understanding of the diverse roles of SCW genes is necessary for the genetic improvement of fast-growing, short-rotation trees that face perennial challenges in their growth and development. Here, we review recent progress into the synergies and antagonisms of SCW development and abiotic stress responses, particularly, the roles of transcription factors, SCW biogenesis genes, and paralog evolution.